1999
DOI: 10.1002/(sici)1096-9896(199909)189:1<72::aid-path401>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic cytokines in mesothelioma: a study of VEGF, FGF-1 and -2, and TGF ? expression

Abstract: Vascular endothelial growth factor (VEGF), acidic and basic fibroblast growth factors (FGF‐1 and ‐2), and transforming growth factor β (TGFβ) are potent angiogenic cytokines. Malignant mesothelioma of the pleura presents with a high intra‐tumoural microvascular density (IMD) which also has prognostic relevance. This study was designed to verify the immunohistochemical expression of the angiogenic cytokines in mesothelioma as well as in non‐neoplastic human mesothelial cells and to study the individual as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(136 citation statements)
references
References 26 publications
2
130
2
Order By: Relevance
“…These include HGF/SF (Tolnay et al, 1998), IL-8 (Antony et al, 1996) and urokinase plasminogen activator (Shetty et al, 1995). VEGF expression was correlated to MVD in MM by Ohta (Ohta et al, 1999) but not in the KumarSingh study (Kumar-Singh et al, 1999). However VEGF expression was not found to be a significant poor prognostic factor in either study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These include HGF/SF (Tolnay et al, 1998), IL-8 (Antony et al, 1996) and urokinase plasminogen activator (Shetty et al, 1995). VEGF expression was correlated to MVD in MM by Ohta (Ohta et al, 1999) but not in the KumarSingh study (Kumar-Singh et al, 1999). However VEGF expression was not found to be a significant poor prognostic factor in either study.…”
Section: Discussionmentioning
confidence: 90%
“…Other biological prognostic markers in MM include the cytokeratin marker Cyfra 21-1 (Schouwink et al, 1999), syndecan-1 (Kumar-Singh et al, 1998), bFGF (Kumar-Singh et al, 1999) and Simian virus-40 sequences (Procopio et al, 2000). We have recently presented data in operable non-small-cell lung cancer indicating that MVD contributes to a biological prognostic model which is independent of TNM stage (Cox et al, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Tumor growth is strongly dependent on angiogenesis (Folkman, 1971). Mesothelioma cells often express VEGF and fibroblast growth factor (bFGF) (Kumar-Singh et al, 1999). Some trials showed patients with malignant pleural mesothelioma expressing serum VEGF concentrations that are higher than with other solid tumors or healthy individuals.…”
Section: Introductionmentioning
confidence: 87%
“…These challenges are reflected in routine diagnostic CT scans, with two recent studies reporting CT sensitivities for pleural malignancy of 68% and 57% [29][30]. In a pilot study, Tsim and colleagues sought to develop a novel perfusionbased MRI biomarker for pleural malignancy that utilises the high spatial resolution provided by MRI; this technique was intended to target typical early features of the pleural tumour micro-environment, including neovascularisation and increases in constituent blood vessel density [31][32].…”
Section: Optimization Of Early Contrast-enhancement Mrimentioning
confidence: 99%